Analisis Hubungan El Niño dengan Kekeringan Meteorologis dan Dampaknya Terhadap Produksi Padi di Provinsi Bali - Putranto, Wahyu Widodo (Stasiun Pemantau Atmosfer Global Bukit Kototabang, 2021)
This research was intended to analyze the relation between the phenomenon of El Niño occurrence and meteorological drought in Bali Province and its effect to the rice production in Bali Province. This research used monthly rainfall of 45 rainfall posts during 1987-2017 period and anomaly data of sea surface temperature (SPL) during 2000-2017 period. In order to know the area drought rate, Standardized Precipitation Index (SPI) was used which was calculated from rainfall post data and the analysis using correlation coefficient method was used. The result was that there was a great strong relation between meteorological drought in Bali Province and the phenomenon of El Niño occurrence. Productivity of rice in the year of El Niño occurrence showed the trend of sustaining the declining in the year of moderate and weak El Niño however the moderate El Niño showed more significant declining trend. Keywords: El Niño, SPI, SPL